Precision agriculture: soybean culture in South Brazil - Marcos Hammerschmidt, José; Karswegaard Pereira Calábria, Zieglenristen; Vinicius Cremonesi, Marcus (Scientia Agraria Paranaensis, 2021)
The objective of describing the scientific production on precision agriculture for soybean cultivation in southern Brazil. Integrative review developed in five stages: 1) to identify research problems: what is the scientific production on precision agriculture for the soybean economy in Brazil, 2) data collection, 3) data evaluation, 4) analysis and interpretation of data and 5) presentation of results. 19 articles appeared, published in the period from 2011 to 2019. All involve the study of soy, created in Latosol, Cambisolo and Argisolo; study areas ranging from 1.74 to 225 hectares; predominance of no-tillage carried out over ten years; crop rotation in summer and winter. As topics addressed: Physiological quality of soybean seeds; Sowing of soybeans; Chemical and physical attributes of the soil; Spectral indices during soybean growth; Weeds and pest control. There was greater emphasis on technologies: digital maps, machinery, tests, computer systems / programs, software, georeferencing, soil analysis, electronic meters, digital images, equipment and optical sensors. The tools used in precision agriculture are important for professional qualification, increased reduction, environmental impacts, sustainability, optimization of time and products and services, cost reduction.